2016
DOI: 10.1007/s40271-016-0184-x
|View full text |Cite
|
Sign up to set email alerts
|

What Outcomes are Important for Gout Patients? In-Depth Qualitative Research into the Gout Patient Experience to Determine Optimal Endpoints for Evaluating Therapeutic Interventions

Abstract: Background and ObjectivesCharacterized by sudden onset of severe joint pain, swelling, redness, and tenderness to touch, gout ‘flare ups’ have a substantial impact on quality of life (QoL). This research employed a patient-centered approach to explore the symptoms and impacts of gout, and assess the content validity of existing patient-reported outcomes (PROs).MethodsQualitative interviews were conducted with 30 US gout patients (non-tophaceous: n = 20, tophaceous: n = 10) and five expert rheumatologists. Each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
33
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 33 publications
4
33
1
2
Order By: Relevance
“…28 Whether the cognitive issues reported by the participants in this study are attributable to age, anemia, 29 The sample size used for this study is typical of concept elicitation interview studies. 22,30,31 Achievement of conceptual saturation in this study indicates that the sample size was sufficient to characterize the burden of PK deficiency from the perspective of patients. It also indicates that it is unlikely any comorbidities or misdiagnoses were the cause of concepts such as jaundice that were reported and also appear in other conditions.…”
Section: Discussionmentioning
confidence: 88%
“…28 Whether the cognitive issues reported by the participants in this study are attributable to age, anemia, 29 The sample size used for this study is typical of concept elicitation interview studies. 22,30,31 Achievement of conceptual saturation in this study indicates that the sample size was sufficient to characterize the burden of PK deficiency from the perspective of patients. It also indicates that it is unlikely any comorbidities or misdiagnoses were the cause of concepts such as jaundice that were reported and also appear in other conditions.…”
Section: Discussionmentioning
confidence: 88%
“…These findings are consistent with international studies. [13][14][15][16][17][18][19][20] Regarding specific findings, the impacts of pain and immobility reported by participants was substantial, as it prevented them from completing necessary work tasks and household chores. and how others perceived their illness.…”
Section: Discussionmentioning
confidence: 99%
“…18 In international studies, financial and occupational concerns were identified by patients with gout as significant impacts. 13,14,[18][19][20] Interestingly, the presented data suggest that in Australia, the financial burden of gout was not a major concern.…”
Section: Discussionmentioning
confidence: 99%
“…A further reason for adopting these dual methods is that some of the students in our population were preparing for examinations, on placements in the UK or on elective placements overseas, which meant that they would not be available for interview at the time the study was conducted. Other studies have shown that qualitative data obtained from written accounts or electronically through a smartphone application can be successfully integrated with interview data to generate novel insights into aspects of health care . Therefore, our approach to data collection was appropriate as it took into account the sensitivity relating to gender identity and afforded students the opportunity to participate in the study as they saw fit irrespective of where they were in their studies.…”
Section: Methodsmentioning
confidence: 99%